2023
DOI: 10.1146/annurev-matsci-081720-112946
|View full text |Cite
|
Sign up to set email alerts
|

Tailor-Made Additives for Melt-Grown Molecular Crystals: Why or Why Not?

Abstract: Tailor-made additives (TMAs) have found a role in crystal morphology engineering and control through specific binding to crystal surfaces through stereochemical recognition. The utility of TMAs, however, has been largely limited to crystal growth from solutions. In this review, we illustrate examples where TMAs have been used to influence the growth of crystals during cooling of their melts. In solution, the crystal growth driving force is governed by solute supersaturation, which corresponds to the deviation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 106 publications
0
16
0
Order By: Relevance
“…Nevertheless, enantiomorphous helices can be correlated with stereogenic building components or the stereochemistry of twist‐inducing additives 20 . Heterochiral helices can also be correlated with enantiomorphous space groups 32 and/or enantiopolar growth directions 16,33,34 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, enantiomorphous helices can be correlated with stereogenic building components or the stereochemistry of twist‐inducing additives 20 . Heterochiral helices can also be correlated with enantiomorphous space groups 32 and/or enantiopolar growth directions 16,33,34 …”
Section: Resultsmentioning
confidence: 99%
“…[51][52][53] Though likely only marginally relevant to spherulitic growth of molecular crystals, helically twisted photonic bundles of silica fibers exploit their dissymmetry to control the orbital angular momentum of light. 54 To test waveguiding in our materials, we must switch from making optical chiroptical measurements of banded spherulites normal to the radial growth direction 22,34,55 to make measurements along the radial growth direction, for example as in Scheme 2. 53 We have previously shown that the CR directed along twisted fibrils of polymers can be especially high at the very center of the polycrystalline ensemble where the fibers are parallel to the wavevector of light.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Typically, one side of a TTF spherulite spins out crystals that twist to the right while the other spins out crystals that twist to the left. This is ultimately determined by the sense of the enantiopolar faces of the crystal that served as the nucleus [70–72] …”
Section: Can Any Molecular Crystal Be Chiral?mentioning
confidence: 99%